Hollow glass microsphere / TPU composite material for life jacket airbag and preparation method thereof
By modifying the hollow glass microbeads and TPU composite materials, the problems of insufficient buoyancy and poor durability of traditional life jacket airbag materials are solved, and the lightweight and self-repairing performance of the materials are achieved, providing more reliable water safety guarantees.
Patent Information
- Application Number
- CN202411632859.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The traditional life jacket airbag material lacks buoyancy, poor durability, and has a large weight. The combination of hollow glass microbeads and TPU is weak, which affects the material performance.
Modified hollow glass microbeads and TPU composite materials are used to enhance the buoyancy, binding force and self-healing properties of the material by introducing cetyl polyoxyethylene ether.
It improves the buoyancy and durability of the life jacket airbag material, enhances the binding force between the hollow glass microbeads and TPU, realizes the lightweight and self-repairing performance of the material, and extends the service life of the material.
Smart Images

Figure CN119143970B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane elastomers, and particularly relates to a hollow glass microbead / TPU composite material for a life jacket airbag and a preparation method thereof. Background Art
[0002] In water rescue and water activities, life jackets are important equipment to protect the lives of people. Traditional life jacket airbag materials usually have problems such as insufficient buoyancy, poor durability, and heavy weight. Thermoplastic polyurethane (TPU) has good elasticity, wear resistance, and chemical corrosion resistance, but the buoyancy of pure TPU material is limited. Hollow glass microspheres have the characteristics of low density and high buoyancy. By compounding hollow glass microspheres with TPU, it is expected to develop a new type of life jacket airbag material, which can give full play to the high buoyancy characteristics of hollow glass microspheres, and use the excellent mechanical properties and durability of TPU to improve the overall performance of life jacket airbags.
[0003] At present, although there have been some studies on the application of composite materials in different fields, there are relatively few studies specifically on hollow glass microspheres / TPU composite materials for life jacket airbags. However, the binding force between unmodified hollow glass microspheres and TPU is weak, which is easy to cause agglomeration during processing and fall off during use, affecting the performance of life jackets.
[0004] Therefore, the development of a hollow glass microsphere / TPU composite material for life jacket airbags and a preparation method thereof has important practical significance and broad market prospects, and can provide more reliable protection for water safety. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a hollow glass microsphere / TPU composite material for life jacket airbags, which is strong, durable and not easy to be damaged. The modified hollow glass microspheres are used to improve the buoyancy of the TPU material and increase the bonding strength between the hollow glass microspheres and TPU. The present invention also provides a preparation method thereof.
[0006] The hollow glass microsphere / TPU composite material for life jacket airbags of the present invention is made of the following raw materials in percentage by mass:
[0007] Polyether diol 48%-61%,
[0008] Diisocyanate 28%-33%,
[0009] Mixed chain extender 5%-9%,
[0010] Hydrolysis resistant agent 0.2%-0.4%,
[0011] Antioxidant 0.3%-0.5%,
[0012] Catalyst 0.2%-0.4%,
[0013] Modified hollow glass microspheres 5%-9%.
[0014] Preferably, the polyether diol is one or more of polyoxypropylene glycol, polytetramethylene glycol, and polyoxyethylene glycol.
[0015] Preferably, the diisocyanate is diphenylmethane diisocyanate (MDI).
[0016] Preferably, the mixed chain extender is 1,4-butanediol (BDO) and 2,2'-dithiodiethanol mixed in a mass ratio of (2-4):1.
[0017] Preferably, the anti-hydrolysis agent is carbodiimide.
[0018] Preferably, the antioxidant is one or more of antioxidant 1024 , antioxidant 1010 , and antioxidant 168 .
[0019] Preferably, the catalyst is one or more of an organic bismuth catalyst, an organic tin catalyst or a titanate catalyst.
[0020] Preferably, the preparation process of the modified hollow glass microspheres is as follows:
[0021] (1) dissolving cetyl alcohol polyoxyethylene ether in distilled water to prepare an emulsion with a mass fraction of 20%-30%, subjecting the emulsion to ultrasonic vibration for 2-4 hours and fully stirring until the cetyl alcohol polyoxyethylene ether is completely dissolved in water, thereby obtaining a solution containing cetyl alcohol polyoxyethylene ether;
[0022] (2) adding hollow glass microspheres to a solution containing cetyl alcohol polyoxyethylene ether, wherein the mass ratio of the hollow glass microspheres to the solution containing cetyl alcohol polyoxyethylene ether is 1:(3-5), and contacting the cetyl alcohol polyoxyethylene ether with the hollow glass microspheres by stirring and ultrasonic vibration for 2-4 hours;
[0023] (3) Filter, wash with ethanol, and dry for 1-2 hours to remove excess cetyl alcohol polyoxyethylene ether to obtain modified hollow glass microspheres.
[0024] The method for preparing the hollow glass microsphere / TPU composite material for life jacket airbags of the present invention comprises the following steps:
[0025] (1) Add polyether diol, hydrolysis resistance agent, antioxidant, catalyst, and modified hollow glass microspheres into reactor A and mix them, place diisocyanate in reactor B and stir, and place mixed chain extender in reactor C;
[0026] (2) The raw materials in reactors A, B, and C are injected into the feeding port of a twin-screw extruder through a metered pouring system. The raw materials are reacted, sheared, and plasticized in the twin-screw extruder at a screw speed of 160-200 r / min and a temperature of 140-210°C. The raw materials are then cut into elliptical particles by an underwater pelletizer.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The introduction of 2,2'-dithiodiethanol chain extender in the mixed chain extender can directly react during the TPU synthesis process, and the introduction of SS bonds can break and re-form under certain conditions, so that TPU has enhanced self-healing and adjustable mechanical properties. At the same time, the chain-extended TPU produces micro-crosslinking, enhances structural tightness and is more stable under ultraviolet radiation, reduces aging and degradation, and is beneficial to the durability of life jacket airbags;
[0029] 2. The molecule of cetyl alcohol polyoxyethylene ether contains O atoms and H atoms. The O atoms have strong electronegativity and can form hydrogen bonds with polar groups such as hydroxyl groups on the surface of glass microspheres. The bond energy of hydrogen bonds can make cetyl alcohol polyoxyethylene ether adhere to the surface of glass microspheres better at the microscopic level, thereby enhancing the bonding force between the two. The oxygen atoms in the TPU ether group can form a dipole-dipole interaction with the oxygen atoms in cetyl alcohol polyoxyethylene ether, thereby enhancing the bonding force between the two. This modification helps to improve the dispersibility and compatibility of glass microspheres and TPU during the composite process without affecting the normal reaction;
[0030] 3. The structure of 2,2'-dithiodiethanol chain extender and the penetration synergistic effect of modified hollow glass microspheres. When subjected to external force, the modified glass microspheres can disperse stress and prevent local stress concentration from causing material rupture, while the TPU molecular chain after 2,2'-dithiodiethanol chain extension can absorb energy through deformation, reducing damage to the life jacket airbag material;
[0031] 4. The preparation method of the present invention is simple and easy to implement and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a scratch surface morphology image of the scratch test sample of Example 1;
[0033] Figure 2 This is a surface morphology picture of the scratch test sample in Example 1 after the scratch was left for 24 hours. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with embodiments.
[0035] All raw materials used in the examples are commercially available unless otherwise specified.3 , average particle size 60μm.
[0036] Example 1
[0037] The hollow glass microsphere / TPU composite material for life jacket airbag is made of the following raw materials in percentage by mass:
[0038] Polytetramethylene glycol: 61%,
[0039] MDI: 28%,
[0040] BDO: 4%,
[0041] 2,2'-dithiodiethanol: 1%,
[0042] Carbodiimide: 0.4%,
[0043] Antioxidant 1024: 0.3%,
[0044] Bismuth 2-ethylhexanoate: 0.3%,
[0045] Modified hollow glass microspheres: 5%.
[0046] Among them, the preparation process of modified hollow glass microspheres is as follows:
[0047] (1) dissolving cetyl alcohol polyoxyethylene ether in distilled water to prepare an emulsion with a mass fraction of 20%, subjecting the mixture to ultrasonic vibration for 2 hours and fully stirring until the cetyl alcohol polyoxyethylene ether is completely dissolved in water, thereby obtaining a solution containing cetyl alcohol polyoxyethylene ether;
[0048] (2) adding hollow glass microspheres to a solution containing cetyl alcohol polyoxyethylene ether, wherein the mass fraction ratio of the hollow glass microspheres to the solution containing cetyl alcohol polyoxyethylene ether is 1:5, and contacting the cetyl alcohol polyoxyethylene ether with the hollow glass microspheres by stirring and ultrasonic vibration for 3 hours;
[0049] (3) Filter, wash with ethanol, and dry for 1 hour to remove excess cetyl alcohol polyoxyethylene ether to obtain modified hollow glass microspheres.
[0050] The method for preparing the hollow glass microsphere / TPU composite material for life jacket airbags comprises the following steps:
[0051] (1) Add polytetramethylene glycol, carbodiimide, antioxidant 1024, bismuth isooctanoate, and modified hollow glass microspheres into reactor A and mix them; place MDI in reactor B and stir; and place mixed chain extender BDO and 2,2'-dithiodiethanol in reactor C;
[0052] (2) The raw materials in reactors A, B, and C are injected into the feeding port of a twin-screw extruder through a metered pouring system, where they are reacted, sheared, and plasticized, and then cut into elliptical particles by an underwater pelletizer; the screw speed is 200 r / min, and the temperatures of each zone of the twin-screw extruder are: the temperature of the front section of the screw is 210°C, the middle section is 200°C, and the temperature of the rear section is 160°C.
[0053] Example 2
[0054] The hollow glass microsphere / TPU composite material for life jacket airbag is made of the following raw materials in percentage by mass:
[0055] Polyoxypropylene glycol: 54%,
[0056] MDI: 30%,
[0057] BDO: 6%,
[0058] 2,2'-dithiodiethanol: 2%,
[0059] Carbodiimide: 0.2%,
[0060] Antioxidant 1010: 0.4%,
[0061] Dibutyltin dilaurate: 0.4%,
[0062] Modified hollow glass microspheres 7%.
[0063] Among them, the preparation process of modified hollow glass microspheres is as follows:
[0064] (1) dissolving cetyl alcohol polyoxyethylene ether in distilled water to prepare an emulsion with a mass fraction of 25%, subjecting the mixture to ultrasonic vibration for 4 hours and fully stirring until the cetyl alcohol polyoxyethylene ether is completely dissolved in water, thereby obtaining a solution containing cetyl alcohol polyoxyethylene ether;
[0065] (2) adding hollow glass microspheres to a solution containing cetyl alcohol polyoxyethylene ether, wherein the mass fraction ratio of the hollow glass microspheres to the solution containing cetyl alcohol polyoxyethylene ether is 1:4, and contacting the cetyl alcohol polyoxyethylene ether with the hollow glass microspheres by stirring and ultrasonic vibration for 4 hours;
[0066] (3) Filter, wash with ethanol, and dry for 1.5 h to remove excess cetyl alcohol polyoxyethylene ether to obtain modified hollow glass microspheres.
[0067] The method for preparing the hollow glass microsphere / TPU composite material for life jacket airbags comprises the following steps:
[0068] (1) Add polyoxypropylene glycol, carbodiimide, antioxidant 1010, dibutyltin dilaurate, and modified hollow glass microspheres into reactor A and mix them, place MDI in reactor B and stir, and place mixed chain extender BDO and 2,2'-dithiodiethanol in reactor C;
[0069] (2) The raw materials in reactors A, B, and C are injected into the feeding port of a twin-screw extruder through a metered pouring system, where they are reacted, sheared, and plasticized, and then cut into elliptical particles by an underwater pelletizer; the screw speed is 180 r / min, and the temperatures of each zone of the twin-screw extruder are: 205°C for the front section of the screw, 195°C for the middle section, and 150°C for the rear section.
[0070] Example 3
[0071] The hollow glass microsphere / TPU composite material for life jacket airbag is made of the following raw materials in percentage by mass:
[0072] Polyoxyethylene glycol: 48%,
[0073] MDI: 33%,
[0074] BDO: 6%,
[0075] 2,2'-dithiodiethanol: 3%,
[0076] Carbodiimide: 0.3%,
[0077] Antioxidant 168: 0.5%,
[0078] Tetrabutyl titanate: 0.2%,
[0079] Modified hollow glass microspheres 9%.
[0080] Among them, the preparation process of modified hollow glass microspheres is as follows:
[0081] (1) dissolving cetyl alcohol polyoxyethylene ether in distilled water to prepare an emulsion with a mass fraction of 30%, subjecting the mixture to ultrasonic vibration for 2 hours and fully stirring until the cetyl alcohol polyoxyethylene ether is completely dissolved in water, thereby obtaining a solution containing cetyl alcohol polyoxyethylene ether;
[0082] (2) adding hollow glass microspheres to a solution containing cetyl alcohol polyoxyethylene ether, wherein the mass fraction ratio of the hollow glass microspheres to the solution containing cetyl alcohol polyoxyethylene ether is 1:3, and contacting the cetyl alcohol polyoxyethylene ether with the hollow glass microspheres by stirring and ultrasonic vibration for 2 hours;
[0083] (3) Filter, wash with ethanol, and dry for 2 hours to remove excess cetyl alcohol polyoxyethylene ether to obtain modified hollow glass microspheres.
[0084] The method for preparing the hollow glass microsphere / TPU composite material for life jacket airbags comprises the following steps:
[0085] (1) Add polyethylene glycol, carbodiimide, antioxidant 168, tetrabutyl titanate, and modified hollow glass microspheres into reactor A and mix them, place MDI in reactor B and stir, and place mixed chain extender BDO and 2,2'-dithiodiethanol in reactor C;
[0086] (2) The raw materials in reactors A, B, and C are injected into the feeding port of a twin-screw extruder through a metered pouring system, where they are reacted, sheared, and plasticized, and then cut into elliptical particles by an underwater pelletizer; the screw speed is 160 r / min, and the temperatures of each zone of the twin-screw extruder are: 200°C for the front section of the screw, 190°C for the middle section, and 140°C for the rear section.
[0087] Comparative Example 1
[0088] The difference between Comparative Example 1 and Example 1 is that the hollow glass microspheres are not modified.
[0089] Comparative Example 2
[0090] The difference between Comparative Example 2 and Example 1 is that BDO of equal mass is used to replace 2,2'-dithiodiethanol.
[0091] Comparative Example 3
[0092] The difference between Comparative Example 3 and Example 1 is that the hollow glass microspheres are not modified, and an equal mass of BDO is used instead of 2,2'-dithiodiethanol.
[0093] Comparative Example 4
[0094] The difference between Comparative Example 4 and Example 1 is that modified hollow glass microspheres and 2,2'-dithiodiethanol are not added to the formula.
[0095] Performance Testing
[0096] The particles prepared in Examples 1-3 and Comparative Examples 1-4 were molded into 2 mm thick standard test pieces using an injection molding machine to test hardness, tensile strength, and specific gravity. A 0.2 mm film was made using a film drawing machine for scratch testing. The test items and test methods are as follows:
[0097] (1) Tensile strength test: ASTM D412 standard is implemented;
[0098] (2) Specific gravity test: Use a density balance to test the specific gravity;
[0099] (3) Hardness test: Implementation of ASTM-2240 standard;
[0100] (4) Scratch test: Perform a scratch test with a utility knife under a pressure of 1kg on a customized device and observe the scratch condition.
[0101] Specific performance test indicators are shown in Table 1:
[0102] Table 1 Performance test table of Examples 1-3 and Comparative Examples 1-4
[0103]
[0104] As can be seen from Table 1, the introduction of hollow glass microspheres modified with cetearyl alcohol polyoxyethylene ether reduces the specific gravity of TPU material by about 15%, making the material lighter. At the same time, the introduction of mixed chain extender 2,2-dithiodiethanol can adjust the segment structure of TPU. Since its molecules contain disulfide bonds, the extended TPU segments cooperate with the modified hollow glass microspheres to self-repair the TPU material. When the TPU material is subjected to external force and cracks are generated, the disulfide bonds can be broken and reformed under appropriate conditions to achieve self-repair of the cracks, such as Figure 1 , Figure 2 As shown, the scratch test of Example 1 shows that the scratch can be self-recovered after 24 hours. This self-repairing property can extend the service life of TPU materials, improve their reliability, and provide a new idea and method for preparing high-performance life jacket airbag materials.
Claims
1. A hollow glass microsphere / TPU composite material for life jacket airbags, characterized in that: Made from the following raw materials in percentage by mass: Polyether diol 48%-61%, Diisocyanate 28%-33%, Mixed chain extender 5%-9%, Hydrolysis resistant agent 0.2%-0.4%, Antioxidant 0.3%-0.5%, Catalyst 0.2%-0.4%, Modified hollow glass microspheres 5%-9%; The mixed chain extender is 1,4-butanediol and 2,2'-dithiodiethanol mixed in a mass ratio of (2-4):1; The preparation process of modified hollow glass microspheres is as follows: (1) dissolving cetyl alcohol polyoxyethylene ether in distilled water to prepare an emulsion with a mass fraction of 20%-30%, subjecting the emulsion to ultrasonic vibration for 2-4 hours and stirring until the cetyl alcohol polyoxyethylene ether is dissolved in water, thereby obtaining a solution containing cetyl alcohol polyoxyethylene ether; (2) adding hollow glass microspheres to a solution containing cetyl alcohol polyoxyethylene ether, wherein the mass ratio of the hollow glass microspheres to the solution containing cetyl alcohol polyoxyethylene ether is 1:(3-5), and contacting the cetyl alcohol polyoxyethylene ether with the hollow glass microspheres by stirring and ultrasonic vibration for 2-4 hours; (3) Filter, wash with ethanol, and dry for 1-2 hours to obtain modified hollow glass microspheres.
2. The hollow glass microsphere / TPU composite material for life jacket airbag according to claim 1, characterized in that: The polyether diol is one or more of polyoxypropylene glycol, polytetramethylene ether glycol and polyoxyethylene glycol.
3. The hollow glass microsphere / TPU composite material for life jacket airbag according to claim 1, characterized in that: The diisocyanate is diphenylmethane diisocyanate.
4. The hollow glass microsphere / TPU composite material for life jacket airbag according to claim 1, characterized in that: The anti-hydrolysis agent is carbodiimide.
5. The hollow glass microsphere / TPU composite material for life jacket airbag according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1024 , antioxidant 1010 , and antioxidant 168 .
6. The hollow glass microsphere / TPU composite material for life jacket airbag according to claim 1, characterized in that: The catalyst is one or more of an organic bismuth catalyst, an organic tin catalyst or a titanate catalyst.
7. A method for preparing the hollow glass microsphere / TPU composite material for life jacket airbags according to any one of claims 1 to 6, characterized in that: The steps include: (1) Add polyether diol, hydrolysis resistance agent, antioxidant, catalyst, and modified hollow glass microspheres into reactor A and mix them, place diisocyanate in reactor B and stir, and place mixed chain extender in reactor C; (2) The raw materials in reactors A, B, and C are injected into the feeding port of the twin-screw extruder through a metered pouring system, reacted, sheared, and plasticized in the twin-screw extruder, and cut into elliptical particles by an underwater pelletizer.
Citation Information
Patent Citations
Polyurethane floating material and preparation method thereof
CN107573482A
Manufacturing method of self-repairing invisible car cover film
CN118420950A